INCLUSIVITY, DIVERSITY, AND JOB SATISFACTION OF EMPLOYEES IN THE AIRLINE INDUSTRY - Del Villar, Juan Rodrigo; Chockdee, Amonthep; Duangchankham, Namthip; Tanthuean, Phiyanan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
Diversity and inclusivity are vital for job satisfaction as they enhance employee performance and service quality. This study explores how these practices affect job satisfaction among airline industry employees, focusing on Thai Airways International. While previous research has emphasized the importance of diversity and inclusivity, there is limited data specific to the airline sector. This research fills that gap by analyzing data from 100 employees using descriptive and inferential statistics. The findings indicate that the company’s commitment to diversity and anti-discrimination policies significantly boosts job satisfaction and performance, leading to increased productivity, fewer distractions, and higher motivation for skill development and career advancement. Recommendations include prioritizing diversity through targeted recruitment, comprehensive training, and regular policy reviews, as well as fostering open communication and team bonding to mitigate job insecurity and enhance camaraderie.